Does corruption matter for the environment? Panel evidence from China - Xianchun Liao; Eyup Dogan; Jungho Baek (Economics: The Open-Access, Open-Assessment E-Journal, 2017)
This article examines the income-energy-SO2 emissions nexus by taking a corruption variable into account. To that end, the panel cointegration methods are applied to 29 Chinese provinces over 1999-2012. The authors' empirical evidence shows that an increase in the number of anti-corruption cases tends to drive down SO2 emissions in China. It is also found that income growth appears to have a beneficial effect on decreasing SO2 emissions over the past two decades. Finally, energy consumption is found to increase SO2 emissions.
Keywords: C23; Q56; 330; China; corruption; environment; EKC; panel; SO2